Descriptive study of Rhabditis freitasi nematodes taken from Gir cattle with severe otitis in northern Brazil - Silva, Francirley Monteiro e; Santos, Francisco Glauco de Araújo; Montoya-Flórez, Luis Mauricio [UNESP]; Rocha, Noeme Sousa [UNESP]; Diniz, Jefferson Viana Alves (My University, 2013)
Otitis induced by rhabditiform nematodes in Gir and Indubrasilhas cattle has been reported in several states of Brazil. Nematodes eggs, larvae and adults of both sexes rhabditis freitasi were taken from infested Gir cattle suffering severe ottorhea and examined microscopically and morphologically. Affected cattle presented purulent secretions from external ear canals, shook their heads, appeared irritable and were sensitive to handling. Findings suggest that the condition proliferates through introduction of parasitic-infested animals from endemic areas. Parasite data was analyzed through descriptive statistics and findings are reported.
Keywords: Rhabditis; Parasitic otitis; Cattle Gir breed